How do crystal shapes of nano-ceria determine its ketonization performance during biomass pyrolysis? - Wan, Yiling; Ding, Kuan; Lam, Jason Chun-Ho; Zhong, Daoxu; Zhang, Shu (Fuel processing technology, 2023)
Catalytic pyrolysis of biomass over CeO2 to prepare ketonic chemicals is an important way to achieve carbon emission reduction, whereas the role of catalyst structure has long been overlooked. In this work, nano-CeO2 with different crystal shapes, namely nanorods (R-CeO2), nano-polyhedra (P-CeO2), and nanocubes (C-CeO2), were synthesized and then tested in catalytic ketonization of xylan. Results showed that among all the three catalysts, C-CeO2 produced the highest yield of ketones. Characterization results revealed that C-CeO2 presented the lowest content of oxygen vacancies while exhibiting the highest proportion of {100} facets, proving that the {100} facets made a greater contribution to the total yield of ketones. On the other hand, P-CeO2 and R-CeO2 displayed a better selectivity to linear ketones, which was beneficial to improving the product quality. The relative contents of {111} facets of these catalysts were higher than C-CeO2, demonstrating that the {111} facets could selectively produce linear ketones. The proposed mechanism indicated that P-CeO2 and R-CeO2 principally enhanced the ketonic deoxygenation reactions, while C-CeO2 also promoted the recyclization reaction, producing more cyclic ketones. These findings disclose that the {111} facets of CeO2 are more favorable to producing valuable linear ketones. [Display omitted] •The relationship between CeO2 crystal shapes and ketonization ability was established.•CeO2 nanocubes produced the highest yield of ketones during xylan pyrolysis.•{100} facets of CeO2 promoted the recyclization reaction to produce cyclic ketones.•CeO2 nanorods and nano-polyhedra showed a better selectivity to linear ketones.•{111} facets were responsible for the selectivity of nanorods and nano-polyhedra.